Translational biophysics: the physical sciences in molecular medicine. (November 2010) - Ryadnov, Maxim G; Cerasoli, Eleonora; Martyna, Glenn J; Crain, Jason
Traditional approaches of medicinal chemistry focus on finding novel structures possessing desired biological properties, or on relating chemical details to a particular biological function. Here the aim is to hit the therapeutic target of interest rather than to understand and exploit its origin. Consequently, molecular mechanisms underlying the disease are of much lesser concern, with intuitive designs continuing to be most successful. Physical sciences can offer alternative ways of tackling the problem by establishing structural continuums between different time and length scales spanning physical phenomena of life processes and their disorders. This can be achieved by the use of approximated physical models providing a rationale for interconversions between different but related scales, which can further be extended with chemical details obtained from complementary experimental data.